Children's conversion of cultural capital into educational success: the symbolic and skill-generating functions of cultural capital. Issue 2 (17th February 2020) - Mikus, Karoline; Tieben, Nicole; Schober, Pia S.
Abstract: A prominent explanation of intergenerational educational inequality is Bourdieu's cultural reproduction theory. Indeed, previous studies have frequently shown that children's cultural capital relates to academic outcomes. However, it remains unclear how children convert their cultural capital into achievement. While Bourdieu argued that cultural capital influences academic outcomes primarily by biasing teachers' grades, other researchers have proposed the alternative explanation that children's cultural capital absorption directly translates into academic skills. Using survey data on 2975 fifth graders from the German National Educational Panel Study, we disentangle these two mechanisms of children's cultural capital conversion; and argue that the main conversion mechanism depends on the cultural capital dimension examined. The results of our structural equation model suggest that both mechanisms are at work and that the main conversion mechanism depends on the dimension of cultural capital examined.